Motor City movie culture, 1916-1925 - Abel, Richard, 1941- (Bloomington, Indiana : Indiana University Press, Office of Scholarly Publishing, Herman B Wells Library, 2020)
"Motor City Movies, 1916-1925 is a broad textured look at Hollywood coming of age in a city with a burgeoning population and complex demographics. Richard Abel investigates the role of local Detroit organizations in producing, distributing, exhibiting, and publicizing films in an effort to make moviegoing part of everyday life. Tapping a wealth of primary source material-from newspapers, spatiotemporal maps, and city directories to rare trade journals, theater programs, and local newsreels-Abel shows how entrepreneurs worked to lure moviegoers from Detroit's diverse ethnic neighborhoods into the theaters. Covering topics such as distribution, programming practices, nonfiction film, and movie coverage in local newspapers, with entr'actes that dive deeper into the roles of key individuals and organizations, this book examines how efforts in regional metropolitan cities like Detroit worked alongside California studios and New York head offices to bolster a mass culture of moviegoing in the United States"--
Mapping circulation in Detroit's movie market -- Movies, live acts, and the theatrical experience : programming practices in the Motor City -- "Detroit-made" newsreels and other short nonfiction films -- Motor City menus for movie fans.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
JSTOR
Keywords: Motion picture theaters -- Michigan -- Detroit -- History -- 20th century; Motion picture audiences -- Michigan -- Detroit -- History -- 20th century; Motion pictures -- Social aspects -- Michigan -- Detroit; Cinéma -- Publics -- Michigan -- Detroit -- Histoire -- 20e siècle.; Cinéma -- Aspect social -- Michigan -- Detroit; ART -- Film & Video; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion picture audiences; Motion picture theaters; Motion pictures -- Social aspects; Michigan -- Detroit; 1900-1999; History